Trapped between Desire and Duty: Neurosis as a Lens for Edna’s Struggles in The Awakening (RR Interdisciplinary Journal, 2024)
This article examines Kate Chopin’s The Awakening (2011) through the lens of neurosis, concentrating on Edna Pontellier’s actions and reactions as she navigates the incompatible demands of societal expectations and her personal desires. Drawing on psychoanalytic theories, this article explores Edna’s journey as a reflection of the continued neurosis characterized by repression, anxiety, and emotional turmoil. Edna is portrayed as a woman torn between her roles as a wife or mother or both and her yearning for personal freedom and self-expression. This inner conflict propels her beyond the circumference of the circle of the societal expectations, leading her to a suffocating atmosphere. The analysis reveals the devastating consequences of attempting to assert individuality, especially by women, ignoring the long cemented patriarchal framework. It stresses the tension between her longing for autonomy and the limiting social norms of the 19th century America, leading to her ultimate psychological breakdown. By framing Edna’s conflicting acts as a manifestation of neurosis, this article exposes how Kate Chopin portrays the cost of non-conformity and the psychological toll of seeking individuality in a patriarchal society. The article also explores how personal experiences and the cultural conditions collectively generate neurosis. This perspective underscores the intricate interplay between personal psychology and societal restrictions, offering new insights into Edna’s tragic life trajectory and Chopin’s critique of gender norms.